STRATEGI KOMUNIKASI KEPOLISIAN SEKTOR KECAMATAN SIMPANG KANAN KABUPATEN ROKAN HILIR DALAM MENCEGAH PENYALAHGUNAAN NARKOBA BAGI REMAJA - Kartika "; Rusmadi Awza (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2022)
The number of criminal cases committed by teenagers, especially drug abuse, so that the intersection right sector police have a goal to change the pattern and behavior of teenagers so they don't commit drug abuse crimes. This program has received a lot of appreciation and positive response from the community. The purpose of this study was to determine the communicator selection strategy, message delivery strategy, media se- lection strategy, audience determination strategy, and the response to the Simpang Right Police Station in tackling drug use for adolescents.This study uses a qualitative approach with a descriptive method. the technique of determining the research subject using the purposive technique. The informants in this study were the head of the Simpang Right Police as the head of the Simpang Right Police who knew various communication strategies carried out by the communicator, the Head of Criminal Investigation Unit of the Simpang Right Police as a communicator in the field, five community leaders from the subdistrict head, village head, RT, RW, the head of Karang Taruna, three people. elder of three drug users. The data collection techniques used were interviews, observation, and documentation. The data analysis technique is Miles and Huberman Interactive. To achieve the validity of the data in this study, the researchers used extended participation, triangulation and peer-checking in discussions.Based on the results of the research that the researchers have done, the results of the research to identify the problem, the first result is the strategy of selecting a communicator in preventing drug abuse for adolescents in accordance with credibility, education, experience and attractiveness. The strategy for delivering messages is in the form of informative messages found in online media and social media, persuasive mes- sages are found in banners or slogans and educative messages are found in socializa- tion and counseling activities. The media selection strategy used was social media such as Facebook @polsek Simpang Kanan and Instagram @Humas_Polsek_Simpang_Kanan, while online media used were www.riauoposition.com, www.gerbangriau.com, www.jurnalpolri.com. The audience selection strategy is all youth and the general public of Simpang Kanan sub-district. Then related to the last identification is the response, where the response related to the strategy conveyed is a positive response from the Simpang Kanan community, namely that they participate in preventing drug abuse for teenagers so that the Simpang Kanan sector police find it easier to carry out their communication strategy.